High-dose Chemotherapy in Germ Cell Cancer Patients With Brain Metastases: Experience of an Expert Center. (August 2021) - Delaye, Matthieu; Benderra, Marc-Antoine; Deforceville, Louise; Larghero, Jérôme; Parquet, Nathalie; Culine, Stéphane; Grazziotin-Soares, Daniele; Lotz, Jean-Pierre
Abstract : Objectives: Germ cell tumor (GCT) patients with brain metastases (BM) have a poor prognosis and high risk of treatment failure. Optimal therapies for these patients remain controversial. The aim of this study was to report the outcomes of all GCT patients with BM treated with high-dose chemotherapy (HDCT) in our French expert center for GCT. Methods: We carried out a retrospective study of 35 GCT patients with BM who were treated from 2003 to 2019 with HDCT, followed by infusions of autologous peripheral blood hematopoietic stem cells. Results: The overall survival at 2 years was 36.9% (95% confidence interval, 19.7-54). The median overall survival was 12 months and the median progression-free survival was 8 months. No variables were associated with better survival in the univariable analysis. Among the 35 patients included in our study, 31 completed HDCT and 4 stopped treatments after mobilization. Eleven patients (11) showed favorable responses (complete, partial, or stable disease) to HDCT and 20 patients died of disease progression (17) or toxicities (3). Among the 11 patients with favorable responses to HDCT, 8 (72.7%) had metachronous BM, mostly isolated. The majority of these patients did not receive local treatment at diagnosis or at relapse. Conclusions: Together, our study reveals that GCT patients can experience long-term survival even in the presence of BM. Metachronous BM can also be cured with HDCT even in the absence of local treatment. Biological and radiologic responses to mobilization could be a predictor of favorable responses to HDCT.